An innovative approach for the design of cryogenic electrical and process control systems at CERN: the cryogenic Continuous Integration project. Issue 1 (1st May 2022) - Barbe, T; Pezzetti, M; Martin, S; Tovar-Gonzalez, A; Fluder, C
Abstract: Designing, building, commissioning, operating and maintaining multiple complex cryogenics process control systems involves many challenges. For several years, CERN has developed various solutions to help with the whole lifecycle of a cryogenic process control system. This has allowed the production of quality and highly reliable cryogenic control and electrical systems. This paper will present the use of these innovative and automated tools and their evolution; focusing in the first part on continuous integration practices applied to the production of Programmable Logic Controller (PLC) software. The second part will develop the practical applications for software upgrades implemented for the cryogenics processes of non-LHC detectors and test facilities at CERN. Finally, a detailed description of the approach to a standardized generation of electrical drawing for cryogenic systems will be presented along with concrete solutions already successfully implemented in operation.